Derivation and validation of the SLE Disease Activity Score (SLE-DAS): a new SLE continuous measure with high sensitivity for changes in disease activity. Issue 3 (9th March 2019) - Jesus, Diogo; Matos, Ana; Henriques, Carla; Zen, Margherita; Larosa, Maddalena; Iaccarino, Luca; Da Silva, José António Pereira; Doria, Andrea; Inês, Luís Sousa
Abstract : Objectives: To derive and validate a new disease activity measure for systemic lupus erythematosus (SLE), the SLE Disease Activity Score (SLE-DAS), with improved sensitivity to change as compared with SLE Disease Activity Index (SLEDAI), while maintaining high specificity and easiness of use. Methods: We studied 520 patients with SLE from two tertiary care centres (derivation and validation cohorts). At each visit, disease activity was scored using the Physician Global Assessment (PGA) and SLEDAI 2000 (SLEDAI-2K). To construct the SLE-DAS, we applied multivariate linear regression analysis in the derivation cohort, with PGA as dependent variable. The formula was validated in a different cohort through the study of: (1) correlations between SLE-DAS, PGA and SLEDAI-2K; (2) performance of SLEDAI-2K and SLE-DAS in identifying a clinically meaningful change in disease activity (ΔPGA≥0.3); and (3) accuracy of SLEDAI-2K and SLE-DAS time-adjusted means in predicting damage accrual. Results: The final SLE-DAS instrument included 17 items. SLE-DAS was highly correlated with PGA (r=0.875, p<0.0005) and SLEDAI-2K (r=0.943, p<0.0005) in the validation cohort. The optimal discriminative ΔSLE-DAS cut-off to detect a clinically meaningful change was 1.72. In the validation cohort, SLE-DAS showed a higher sensitivity than SLEDAI-2K (change ≥4) to detect a clinically meaningful improvement (89.5% vs 47.4%, p=0.008) or worsening (95.5% vs 59.1%, p=0.008), while maintaining similar specificities. SLE-DAS performed better in predicting damage accrual than SLEDAI-2K. Conclusion: SLE-DAS has a good construct validity and has better performance than SLEDAI-2K in identifying clinically significant changes in disease activity and in predicting damage accrual.